PENCEGAHAN DAN SIMULASI DETEKSI DINI VERTIGO DI MESJID BAITURRAHMAN LEUWISARI - Henri Setiawan; Reffi Nantia Khaerunnisa; Heri Ariyanto; Fidya Anisa Firdaus (P3M Universitas Aisyiyah Surakarta, 2022)
Vertigo is a sensation of movement from the body like turning without actual rotation. Vertigo is not always caused by a dangerous disease, but in the long term and if not treated immediately vertigo will cause some adverse effects on quality of life to death. This counseling activity aims to introduce the concept of vertigo, signs and symptoms and practice ways to recognize and eliminate the symptoms of vertigo to the Aisyiyah women's group in Leuwisari sub-district. The outreach activities were carried out by way of explanation and discussion on 65 members of Aisyiyah in the Leuwisari sub-district at the Baiturrahman mosque on October 4, 2019. Before and after the counseling, participants were given a questionnaire to evaluate the activities as a measure of the success of the activity. In this health education activitites the participants of the activity gained increased knowledge compared to before the implementation of health education was given. The results of this activity showed that 62% of participants gave a very good assessment and 21% gave a good level of health education activities about vertigo. The author suggests that this activity can be carried out routinely to community groups by the local public health center.